Sports incentive law: Analysis of the gold kimono judo project - Olivio Junior, José Alfredo [UNESP]; Pasqualoto, Bruno Bohm [UNESP]; Gnecco, José Roberto [UNESP]; Mazzei, Leandro Carlos; Nunes, Hudson Fabricius Peres [UNESP]; Drigo, Alexandre Janotta [UNESP] (Universidade Estadual de Maringa, 2021)
The aim of the study was to analyze the judo project Kimono de Ouro from 2011 to 2017, based on resources promoted by the Sports Incentive Law and the application of the national performance sport policies model. The qualitative and descriptive study was carried out through documentary analysis and comparing to the model of Sports Policy Factors Leading to International Sporting Success. From the perspective of sports performance, the results show by the Sports Incentive Law improved the project and show significant correlations with Sports Policy Factors Leading to International Sporting Success. In colclusion, fundraising, financial management and the qualification of the multidisciplinary team were fundamental for the evolution of sports performance.
Lei de incentivo ao esporte: Análise do projeto de judô kimono de ouro
Keywords: Judo; Performance; Professional formation; Sport